Impact of value-based care on quality of life, clinical outcomes, patient satisfaction, and enhanced financial protection among hypertensive patients in Ghana: A protocol for a mixed method evaluation, 2024. - Duah Dwomoh; Gifty Sunkwa-Mills; Kwasi Owusu Antwi; Maxwell Akwasi Antwi; Tobias Floris Rinke de Wit (PLoS ONE)
Background Evidence on which hypertensive intervention is cost-effective is essential to inform strategy, policy development, practice, implementation, and resource allocation. Value-Based Care (VBC) is a healthcare delivery model that emphasizes improving patient outcomes while optimizing costs. It shifts the focus from the volume of services provided to the value delivered to patients. We hypothesize that innovative VBC intervention would be more cost-effective compared to standard care among individuals with poorly controlled hypertension. Methods This study in Ghana will employ a mixed-methods evaluation design, a comprehensive and thorough approach that combines quantitative and qualitative methods. The quantitative component will involve a quasi-experimental study to measure the impact of the VBC intervention on quality of life, improved clinical outcomes, patient satisfaction, and enhanced financial protection among hypertensive patients registered with the National Health Insurance Authority. We will use a difference-in-difference analytic approach and a generalized estimation equation model with cluster-robust standard errors to quantify the impact of VBC, accounting for potential confounding variables. The qualitative component will involve in-depth interviews and focus group discussions to gather insights into the experiences and perceptions of the patients, caregivers, and policymakers involved in the VBC intervention and the benefits, barriers, costs of treatment, and challenges associated with the VBC intervention. Discussions Despite the availability of safe treatment options for hypertension, most people with hypertension in LMICs do not have it controlled. There is currently a paucity of knowledge about the cost-effectiveness of VBC interventions in developing countries. This study aims to fill this knowledge gap and pave the way for more cost-effective hypertension treatment worldwide. The Ghana VBC intervention described in this paper is a pioneering approach to achieving safer, more consistent, and cost-effective care for hypertensive patients.